Community Empowerment In Tourism Development : Concepts And Implications - Ginanjar, Retno (The Eastasouth Management and Business, 2023)
Tourism is a sector that provides income for the country's economy. One of the tourism management concepts that can be applied with local communities is known as Community-Based Tourism (CBT). The basic principle of Community-based Tourism is to make the community the main actor through empowering various tourism activities and maximizing the benefits of tourism for the community. The successful development of Community-Based Tourism has a positive impact on economic, social, cultural, political and environmental aspects.